1999
DOI: 10.1017/s0950268899002204
|View full text |Cite
|
Sign up to set email alerts
|

The shift of genetic subtypes of Escherichia coli O157[ratio ]H7 isolates from cattle

Abstract: A total of 46 Escherichia coli O157:H7 isolates were obtained from sequential faecal samples from seven cattle collected over periods of 2 months. Nine closely related genetic subtypes, determined by pulsed-field gel electrophoresis types using three kinds of restriction endonuclease were observed among the isolates. Distinguishable, but closely related genetic subtypes can be isolated from one farm, or from one cow, should be considered when undertaking an epidemiological survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 12 publications
(18 reference statements)
3
30
0
Order By: Relevance
“…It is unclear whether the source was of bovine or human origin, since both cattle and humans can excrete multiple subtypes (2,3,10,28). One hypothesis is that cow manure contaminated with E. coli O157:H7 was carried into the dormitory on muddy boots, was washed into the septic system, and subsequently seeped into well 6 (Ackelsberg et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear whether the source was of bovine or human origin, since both cattle and humans can excrete multiple subtypes (2,3,10,28). One hypothesis is that cow manure contaminated with E. coli O157:H7 was carried into the dormitory on muddy boots, was washed into the septic system, and subsequently seeped into well 6 (Ackelsberg et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the predominant PFGE patterns, 1 and 1a, have rarely been detected by our laboratory, suggesting that this outbreak originated primarily from a single genetically related strain. Studies have demonstrated that multiple subtypes can be shed from both bovine and human infections (2,3,10,28). Although this is often explained by a loss of either the 60-MDa plasmid or the bacteriophage harboring the Shiga toxin genes, the exact mechanisms involved are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, this differs from the findings of LeClerc et al (18) suggesting that some O157 strains may become hypermutable, making them more adaptable to changing environments and increasing the organism's genetic diversity. Also, a Japanese study (1) reported the shift of genetic subtypes on one farm and from one animal. Although there is some evidence that clonal turnover , X43 2 52 X1, X2, X3, X4, X12, X15, X16, X39, X44, X45 3 35 X5, X19, X20, X21, X24, X26, X30, X32, X33, X36, X37, X40, X41 4 26 X46, X47, X48, X49, X50, X51, X52, X53, X54, 5 8 X7, X31, X54, X56 6 9 X10, X22, X42, X54 7 1 X13 8 29 X8, X11, X25, X30, X59 9 54 X17, X23, X24, X26, X27, X28, X34, X35, X38 10 4 X24, X36 11 7 X6, X8, X9, X18 and genetic rearrangement remain rare under environmental situations, it is possible that this is faster in situ than in the laboratory (12).…”
mentioning
confidence: 99%
“…In addition, in the case of PFGE, the changing of a few bands during cultivation of the STEC strain, even between the same clones, has been observed (14,51). It has been also reported that RFLP patterns of PFGE change even after strain passage through cow or human gastrointestinal tract (1,2,21). If the Region V in the Stx phage is stable, this can be averted.…”
Section: Fig 3 (A)mentioning
confidence: 96%